2023
DOI: 10.1590/1984-70332023v23n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study revealed genetic loci for resistance to fusarium wilt in tomato germplasm

Abstract: Tomato Fusarium wilt caused by Fusarium oxysporum f.sp. lycopersici (Fol) constrains tomato production worldwide. Three hundred forty tomato accessions were evaluated for Fusarium wilt resistance and single nucleotide polymorphisms (SNPs) associated with resistance. The disease resistance evaluation revealed that 15, 13, and 15 accessions were identified as Fusarium wilt resistant in Test 1, 2, and Mean data, respectively, with the disease severity index (DSI) ranging from 0-16.7%. A genome-wide association st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…A total of 17 QTLs were identified at different genomic locations when wheat cultivars were evaluated in a greenhouse against four pathotypes of the stripe rust pathogen [19], while Liu et al [20] documented 14 loci associated with stripe rust in multiple locations, as well as 37 loci with a significant association with the disease at all plant developmental stages. Further, Kawicha et al [21] identified six unique significant SNPs for tomato fusarium wilt resistance located on chromosomes 2, 4, and 7 of the tomato genome. We hypothesized that SNPs associated with the leaf blight response could be identified, and that these SNPs might have a role in host defense.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 17 QTLs were identified at different genomic locations when wheat cultivars were evaluated in a greenhouse against four pathotypes of the stripe rust pathogen [19], while Liu et al [20] documented 14 loci associated with stripe rust in multiple locations, as well as 37 loci with a significant association with the disease at all plant developmental stages. Further, Kawicha et al [21] identified six unique significant SNPs for tomato fusarium wilt resistance located on chromosomes 2, 4, and 7 of the tomato genome. We hypothesized that SNPs associated with the leaf blight response could be identified, and that these SNPs might have a role in host defense.…”
Section: Introductionmentioning
confidence: 99%